2023
DOI: 10.3847/1538-4357/ad0b71
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Quasi-parallel Shock Front

Michael A. Balikhin,
Michael Gedalin,
Simon N. Walker
et al.

Abstract: The aim of this study is to compare observations of the magnetic field structure of observed quasi-parallel collisionless shock fronts with the results obtained analytically. A two-fluid analytic model of the shock front structure was derived under the assumptions that the shock is stationary and planar. The ion and electron kinetic pressures were assumed to be scalar, and polytropic state equations were used. The results of this analytical approach show that the shock magnetic field has an oscillatory structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This finding is in line with theoretical predictions (Gedalin 1998;Gedalin et al 2015), which suggest that a quasi-parallel shock becomes oblique, even quasi-perpendicular, due to the increase in transversal magnetic field amplitude in the ramp-overshoot region. However, prior to our study, observational support for this was limited (Balikhin et al 2023). We have clearly demonstrated that the enhancement of the transversal magnetic field at the ramp overshoot leads to a quasi-perpendicular geometry.…”
Section: Structure Of the Quasi-parallel Shock Transitionmentioning
confidence: 68%
“…This finding is in line with theoretical predictions (Gedalin 1998;Gedalin et al 2015), which suggest that a quasi-parallel shock becomes oblique, even quasi-perpendicular, due to the increase in transversal magnetic field amplitude in the ramp-overshoot region. However, prior to our study, observational support for this was limited (Balikhin et al 2023). We have clearly demonstrated that the enhancement of the transversal magnetic field at the ramp overshoot leads to a quasi-perpendicular geometry.…”
Section: Structure Of the Quasi-parallel Shock Transitionmentioning
confidence: 68%